2020
DOI: 10.4274/tjod.galenos.2020.23682
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between oxidative stress and preeclampsia. The serum ischemia-modified albumin levels and thiol/disulfide homeostasis

Abstract: Objective: Preeclampsia (PE) is a dangerous complication of pregnancy and still a major cause of maternal-fetal morbidity and mortality. Its etiology remains largely unknown, but researchers have suggested oxidative stress-mediated inflammation for the same. The purpose of this study is to investigate the relationship between oxidative stress and PE as well as the usability of oxidative stress indicators such as serum ischemia-modified albumin (IMA) levels and thiol/disulfide balance in the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 38 publications
3
7
0
1
Order By: Relevance
“…Consequently, the investigation of serum IMA generated by hypoxia/ischemia-driven oxidative stress can be useful in this matter. 3,25 In our study, we observed significantly elevated serum levels of IMA in severe PE as compared with mild PE and control groups (P 0.001). Our results agreed with those of the study done by Karasin and Cift, 2020, 25 which showed that inflammation and endothelial cell activity in PE may alter the albumin molecule in the plasma of preeclamptic patients and may cause an increase in its levels.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Consequently, the investigation of serum IMA generated by hypoxia/ischemia-driven oxidative stress can be useful in this matter. 3,25 In our study, we observed significantly elevated serum levels of IMA in severe PE as compared with mild PE and control groups (P 0.001). Our results agreed with those of the study done by Karasin and Cift, 2020, 25 which showed that inflammation and endothelial cell activity in PE may alter the albumin molecule in the plasma of preeclamptic patients and may cause an increase in its levels.…”
Section: Discussionsupporting
confidence: 55%
“…2 Unfortunately, the only treatment for PE is still delivery, and PE causes iatrogenic preterm birth in about 15% of pregnancies. 3 PE may be life-threatening for both mother and child and is still a major cause of maternalfetal morbidity and mortality. After preeclamptic pregnancies, the mother may develop premature cardiovascular disease, such as chronic hypertension, ischemic heart disease, and stroke, later in life.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin is an important part of the antioxidant system and IMA formation is related to oxidative stress [ 14 ]. Within the hypoxic environment typical of the preeclamptic placenta, the N-terminal region of albumin has reduced capacity to bind to cobalt and this chemically changed albumin is referred to as IMA [ 14 , 20 ]. Currently, IMA is utilized as an established marker for ischemic heart diseases and approved by the US Food and Drug Authority (FDA) as the first biomarker with specific clinical application [ 35 – 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thiols constitute a class of organic sulfur compounds characterized by the presence of a sulfhydryl functional group (–SH), also known as a thiol group [ 1 , 2 , 3 , 4 ]. In a biological system, thiols are present as albumin thiols, protein-bound thiols, and low-molecular-weight thiols such as cysteine (Cys), homocysteine (Hcy), glutathione (GSH), and cysteinylglycine (Cys-Gly) [ 2 , 4 , 5 , 6 ]. These free thiols are metabolically related [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%